Histone demethylase LSD1-mediated repression of GATA-2 is critical for erythroid differentiation - Guo Y; Fu X; Jin Y; Sun J; Liu Y; Huo B; Li X; Hu X (Dove Medical Press, 2015)
Yidi Guo,1 Xueqi Fu,1,2 Yue Jin,1 Jing Sun,1 Ye Liu,1 Bo Huo,1 Xiang Li,1 Xin Hu1–31School of Life Sciences, Jilin University, 2Key Laboratory for Molecular Enzymology and Engineering of Ministry of Education, Jilin University, 3National Engineering Laboratory of AIDS Vaccine, School of Life Sciences, Jilin University, Changchun, People’s Republic of ChinaBackground: The transcription factor GATA-2 is predominantly expressed in hematopoietic stem and progenitor cells and counteracts the erythroid-specific transcription factor GATA-1, to modulate the proliferation and differentiation of hematopoietic cells. During hematopoietic cell differentiation, GATA-2 exhibits dynamic expression patterns, which are regulated by multiple transcription factors.Methods: Stable LSD1-knockdown cell lines were established by growing murine erythroleukemia (MEL) or mouse embryonic stem cells together with virus particles, in the presence of Polybrene® at 4 µg/mL, for 24–48 hours followed by puromycin selection (1 µg/mL) for 2 weeks. Real-time polymerase chain reaction (PCR)-based quantitative chromatin immunoprecipitation (ChIP) analysis was used to test whether the TAL1 transcription factor is bound to 1S promoter in the GATA-2 locus or whether LSD1 colocalizes with TAL1 at the 1S promoter. The sequential ChIP assay was utilized to confirm the role of LSD1 in the regulation of H3K4me2 at the GATA-2 locus during erythroid differentiation. Western blot analysis was employed to detect the protein expression. The alamarBlue® assay was used to examine the proliferation of the cells, and the absorbance was monitored at optical density (OD) 570 nm and OD 600 nm.Results: In this study, we showed that LSD1 regulates the expression of GATA-2 during erythroid differentiation. Knockdown of LSD1 results in increased GATA-2 expression and inhibits the differentiation of MEL and embryonic stem cells. Furthermore, we demonstrated that LSD1 binds to the 1S promoter of the GATA-2 locus and suppresses GATA-2 expression, via histone demethylation.Conclusion: Our data revealed that LSD1 mediates erythroid differentiation, via epigenetic modification of the GATA-2 locus.Keywords: LSD1, GATA factor switching, histone demethylation